Numerical simulation of the thermal equilibrium of bodies in contact using the Montecarlo method - Estela Urbina, Ronald Omar (2021)
The conditions of compulsory social confinement as a measure to stop the spread of COVID-19 has had repercussions in academic spaces, in this way both students and university teachers are prevented as a health measure from using laboratories, which implies a difficulty for the teaching-learning, especially in subjects that have a considerable practical component or laboratory hours, as is the case of physics courses. It is in this context that the civil engineering students of the V cycle, through the course of numerical methods, developed the numerical simulation of Monte Carlo. For this purpose, several virtual activities were established, such as the realization of a training workshop in programming language; in the same way, the design of a flow diagram or algorithm was carried out and then implemented in BASIC programming codes. The objective of this research is to numerically simulate the thermal behavior of the system, as well as its temporal evolution, by means of a physical model based on energy exchanges. This is based on the behavior of the particles that make up the bodies, which based on their random movement collide or collide with the contact wall, transferring energy. This allows to see the "temporary" evolution of the system until achieving thermal equilibrium; obtaining results that, for larger units of virtual "time", the system tends to achieve its thermal equilibrium, which compared to the theoretical results, increasingly smaller margins of error are achieved. The random behavior of this system makes it suitable to apply the Monte Carlo method, representing this as a learning strategy generating a “virtual laboratory” where significant learning is promoted at low cost.